2019
DOI: 10.1111/nin.12329
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐seeking: A literature review (and an exemplar of stigmatization in nursing)

Abstract: Despite its lack of conceptual clarity and uniform definition, the term drug-seeking is used frequently by nurses from a variety of practice environments. The drugs patients are referred to as seeking are often pain medications. This is important because nursing has widely adopted a patient-centric definition of pain. Nursing also has a robust ethical code that places high value on human dignity and nurses' role in patient advocacy. A review of literature was conducted with the aims of describing whether/how t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
(69 reference statements)
1
6
0
Order By: Relevance
“…As participants noted, EBE were able to directly challenge stereotypes that were often associated with AOD use. (Copeland 2020;Horner et al 2019;Neville & Roan 2014). This is consistent with studies that indicate 'contact-based' education can support educators to challenge assumptions and reduce stigma and discrimination towards marginalized groups (Corrigan et al 2013;Knaak et al 2014).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…As participants noted, EBE were able to directly challenge stereotypes that were often associated with AOD use. (Copeland 2020;Horner et al 2019;Neville & Roan 2014). This is consistent with studies that indicate 'contact-based' education can support educators to challenge assumptions and reduce stigma and discrimination towards marginalized groups (Corrigan et al 2013;Knaak et al 2014).…”
Section: Discussionsupporting
confidence: 85%
“…Although substance use is increasing and associated with serious health and social problems, nurses and nursing students can hold stigmatizing views of PWUD. These views often reflect community stereotypes about PWUD being 'manipulative', 'criminal', and 'drug seeking' (Copeland 2020;Horner et al 2019;Neville & Roan 2014;Smyth et al 2021). The experience of stigma from health professionals creates a secondary health risk for PWUD, as they may be reluctant to access health services or may discharge themselves from treatment against medical advice due to experiences of stigma and discrimination (Simon et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a review of studies spanning three decades (1966–1996) found that many nurses had a positive attitude while a few had a negative attitude towards individuals with substance use disorders (Howard & Chung 2000). Meanwhile, current studies report that nurses' negative attitudes towards consumers with substance use disorders continue to exist (Copeland 2020; Levis et al . 2022; Neville & Roan 2014; Smyth et al .…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the paucity of AOD content in undergraduate and postgraduate nursing programs means that most nurses do not feel confident in caring for individuals with substance dependence (Compton & Blacher, 2020;Ford, 2011;Lovi & Barr, 2009). Nurses also hold stigmatising views about drug use that centre around the notion that AOD patients are manipulative, violent and criminal drug seekers, who are undeserving of care (Copeland, 2020;Horner et al, 2019;Neville & Roan, 2014). Nurses' attitudes towards people who use AOD arguably stem from the 100 year global war on drugs.…”
Section: Introductionmentioning
confidence: 99%